Cook's country best grilling recipes : more than 100 regional favorites, tested and perfected for the outdoor cook - Van Ackere, Daniel (America's Test Kitchen, 2009)
"From America's most trusted test kitchen come regional and classic grilling recipes at their smoky best. The book also tackles all of the best sides, from Memphis chopped coleslaw and fried okra to tomato pie"--Publisher's description.